Antibiotic alternatives: the substitution of antibiotics in animal husbandry? - Cheng, Guyue; Hao, Haihong; Xie, Shuyu; Wang, Xu; Dai, Menghong; Huang, Lingli; Yuan, Zonghui (Frontiers in Microbiology, 2014)
It is a common practice for decades to use of sub-therapeutic dose of antibiotics in food-animal feeds to prevent animals from diseases and to improve production performance in modern animal husbandry. In the meantime, concerns over the increasing emergence of antibiotic-resistant bacteria due to the unreasonable use of antibiotics and an appearance of less novelty antibiotics have prompted efforts to develop so-called alternatives to antibiotics. Whether or not the alternatives could relly replace antibiotics remains a controversial issue. This review summarizes recent development and perspectives of alternatives to antibiotics. The mechanism of actions, applications, and prospectives of the alternatives such as immunity modulating agents, bacteriophages and their lysins, antimicrobial peptides, pro-, pre- and synbiotics, plant extracts, inhibitors targeting pathogenicity (bacterial quorum sensing, biofilm and virulence), and feeding enzymes are thoroughly discussed. Lastly, the feasibility of alternatives to antibiotics is deeply analyzed. It is hard to conclude that the alternatives might substitute antibiotics in veterinary medicine in the foreseeable future. At the present time, prudent use of antibiotics and the establishment of scientific monitoring systems are the best and fastest way to limit the adverse effects of the abuse of antibiotics and to ensure the safety of animal-derived food and environment.